Analisis Bibliometrik dan Perkembangan Penelitian Perbedaan Gender dalam Komunikasi - Samiri, Muliani; Kasman, Nuraeni; Nonci, Nurjannah; Jumriani (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2024)
Research on gender differences in communication can help understand how gender stereotypes affect the way people communicate This study aims to determine the development of research with the theme